Creating & Managing Learning Centers A Thematic Approach - Ingraham, Phoebe Bell. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
Providing a center-oriented classroom takes more than rearranging the furniture. This book offers guidance to teachers in all aspects of creating learning centers in the classroom. The first section, comprised of five chapters, provides information on using small areas of the classroom for specific activities or tasks. Chapter 1 explains different types of centers and what centers offer students. Chapter 2 outlines physical changes in classrooms, including ideas on how to plan the environment, maintain control, and relate learning centers to curricular objectives. Chapter 3 discusses how to teach students to work in learning centers in an active yet productive way. Chapter 4 explains how the teacher can take student interests into consideration and integrate the curriculum to ensure meaningful connections. Chapter 5 discusses assessment strategies to monitor student progress. The second section, containing four chapters, provides advice on setting up specific centers, including suggested activities for each center, materials, and resources. Chapter 6 addresses literacy development centers, including writing, library/reading, language, and journal centers. Chapter 7 addresses cognitive development centers in the areas of math, science, and geography. Chapter 8 covers creative development centers, including an art center, research center, and cooking center. Chapter 9 addresses physical and social/emotional development centers and describes a gross motor/block area and a role play/dramatic center. Twenty reproducible pages are included. (SD)
Availability: Crystal Springs Books, Ten Sharon Road, Box 500, Peterborough, NH 03458-0500; phone: 800-321-0401 ($19.95).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Active Learning; Classroom Design; Classroom Environment; Cognitive Development; Creative Development; Discovery Learning; Educational Facilities Design; Elementary Education; Emotional Development; Experiential Learning; Learner Controlled Instruction; Learning Centers (Classroom); Learning Resources Centers; Literacy Education; Physical Development; Reading Centers; Resource Centers; Skill Centers; Social Development; Student Centered Curriculum; Thematic Approach; Child Centered Education; Guides, Classroom -- Teacher